Association of C-Reactive Protein Level and Short Term Clinical Outcome among Spontaneous Intracerebral Haemorrhage Patients (Journal of National Institute of Neurosciences Bangladesh, 2018)
Background: C-reactive protein is a biomarker among the spontaneous intracerebral haemorrhage patients.Objective: The purpose of this present study was to see the association of CRP level with the short term clinical outcome among spontaneous intracerebral haemorrhage patients.Methodology: This prospective cohort study was conducted in the Department of Neurology at Dhaka Medical College and Hospital, Dhaka, Bangladesh from July 2012 to June 2014 for a period of two (02) years. Patients presented with first ever spontaneous intracerebral haemorrhage with the age group of more than or equal to 18 years with both sexes and hospital admission within 48 hours of onset were included for this study. Admission plasma CRP was measured and study population were divided into group I (plasma CRP≥6 mg/L) and group II (plasma CRP